2011
DOI: 10.1007/s00405-011-1670-3
|View full text |Cite|
|
Sign up to set email alerts
|

Chemosensory function assessed with psychophysical testing and event-related potentials in patients with atrophic rhinitis

Abstract: Atrophic rhinitis (AR) is a chronic inflammation of the nose characterized by an atrophy of the nasal mucosa. This is typically associated with an impaired sense of smell and a subjective sensation of poor nasal breathing. The aim of this study is to assess chemosensory function in patients suffering from AR using psychophysical testings and event-related potentials (ERP) responses. A cohort of nine patients was extensively studied. Eight out of nine had secondary AR sequela of a bilateral total inferior turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Evidence about reduced trigeminal sensitivity in ENS patients can be also found in a study by Huart et al, where in a smaller cohort of patients the authors reported that six out of nine had no trigeminal responses when assessed with event related potentials …”
Section: Discussionmentioning
confidence: 93%
“…Evidence about reduced trigeminal sensitivity in ENS patients can be also found in a study by Huart et al, where in a smaller cohort of patients the authors reported that six out of nine had no trigeminal responses when assessed with event related potentials …”
Section: Discussionmentioning
confidence: 93%
“…Only a single study 21 to date has measured olfaction in ATR (N = 75), and that too was by a nonvalidated technique based on 4 colorless liquid odors, wherein 10% revealed normal olfaction while 90% showed abnormality—of which 30% had mild loss, 24% severe dysfunction, and 36% complete anosmia. A single study 22 on secondary ATR based on validated olfactory tests revealed dysfunction in 7 of 9 patients who underwent total bilateral inferior turbinectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these reports strongly suggest that rhinologists should consider assessment of trigeminal function, especially in patients potentially being prone to develop paradoxical nasal obstruction after surgery, a condition commonly coined as empty nose syndrome (60,61) .…”
Section: Trpm8 Importance For Intranasal Trigeminal Functionmentioning
confidence: 92%